Effect of dietary addition of Denagard (Tiamulin) and CTC (Chlortetracycline) on pig performance immediately after placement in the finishing barn - S Nitikanchana; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 1,313 pigs (PIC 1050 × 337; initially 49 lb) were used in a 35-d study to determine the effects of adding Denagard (Tiamulin) and CTC (chlortetracycline) to feed on pig performance immediately after placement in the finisher barn. Pigs were transported from one nursery facility and placed into the finishing barn without maintaining pen integrity. Immediately after placement in the finishing barn, pens of pigs were weighed and randomly allotted to treatments arranged in a 2 × 2 factorial with main effects of Denagard (0 and 35 g/ton; Novartis Animal Health, Greensboro, NC) and chlortetracycline (CTC; 0 and 400 g/ton). Diets were corn-soybean meal—based and contained 20% bakery and 35% dried distiller's grains with solubles (DDGS). Treatment diets were fed from d 0 to 15 with a common non-medicated diet fed from d 15 to 35. An interaction (P<0.01) was observed for ADFI from d 0 to 15 and for the overall period, with pigs fed the diet without medication and the combination of Denagard and CTC having greater ADFI than either medication alone. Adding antibiotics to the diets also improved F/G from d 0 to 15, with no differences among pigs fed Denagard, CTC, or their combination (Denagard × CTC interaction, P<0.01). Adding Denagard or CTC to diets improved (P<0.01) ADG and F/G from d 0 to 15; however, when the antimicrobials were removed from the diet (d 15 to 35), ADG of pigs previously fed any of the medicated diets decreased (Denadard P<0.01; CTC P<0.06) compared with pigs previously fed the non-medicated diet. Because the advantages in growth performance from d 0 to 15 were lost during the period from d 15 to 35, there were no differences (P>0.15) in overall ADG or F/G. In conclusion, adding Denagard and/or CTC to diets immediately after pig placement in the finisher can improve growth performance, but the performance was not maintained in the subsequent period when pigs were fed non-medicated diets.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; Antibiotics; Chlortetracycline; Denagard; Finishing pig